2007
DOI: 10.1186/bf03352023
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric measurements during the total solar eclipse of 11 August 1999

Abstract: A number of radio experiments were conducted at Ahmedabad (23• N, 73• E) with the aim of studying the ionospheric effects of the total solar eclipse of 11 August 1999. Rapid radio soundings from the ionosonde were made on the eclipse day and on control days. A riometer was operating at 30 MHz, and Àeld strength measurements along the three oblique incidence paths of Colombo-Ahmedabad (11905 kHz), Bombay-Ahmedabad (558 kHz) and Rajkot-Ahmedabad (810 kHz) were also made. A reduction of about 20% was observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 9 publications
4
21
0
Order By: Relevance
“…This is the reason that the TEC values on the eclipse day are appreciably lower than the mean quiet day values in the peninsular India. Although, our results are in agreement with the previously reported decreasing trend of the TEC and ionospheric electron density during various solar eclipses in low (Chandra et al, 1980(Chandra et al, , 1981(Chandra et al, , 2007Vyas et al, 1997;Yeh et al, 1997;Huang et al, 1999;Tsai and Liu, 1999) and mid-latitudes (Boitman et al, 1999;Afraimovich et al, 1998Afraimovich et al, , 2002Jakowski et al, 2008;Krankowski et al, 2008) observed at different times of the day; importance of our work lies in the fact that comparable reductions in TEC and electron density are seen even during early morning eclipse.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is the reason that the TEC values on the eclipse day are appreciably lower than the mean quiet day values in the peninsular India. Although, our results are in agreement with the previously reported decreasing trend of the TEC and ionospheric electron density during various solar eclipses in low (Chandra et al, 1980(Chandra et al, , 1981(Chandra et al, , 2007Vyas et al, 1997;Yeh et al, 1997;Huang et al, 1999;Tsai and Liu, 1999) and mid-latitudes (Boitman et al, 1999;Afraimovich et al, 1998Afraimovich et al, , 2002Jakowski et al, 2008;Krankowski et al, 2008) observed at different times of the day; importance of our work lies in the fact that comparable reductions in TEC and electron density are seen even during early morning eclipse.…”
Section: Resultssupporting
confidence: 93%
“…The electron density profile on the eclipse day shows reduced electron density in the height range 100-800 km. In an earlier work (Chandra et al, 2007), reduction of the F region electron density has been mentioned in connection with the eclipse of August 1999 in the Indian zone.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…, for the annular solar eclipse of 15 January 2010, showed a reduction of 20 % in the total electron content at Bangalore. The decreasing trends of the ionospheric electron density and total electron content have been reported for different solar eclipse from low latitudes (Chandra et al, 1980(Chandra et al, , 1981(Chandra et al, , 2007Vyas et al, 1997;Yeh et al, 1997), but the importance of present study lies in the fact that comparable reductions in TEC have been observed at four places located on different latitudes and longitudes. The ionization density and the total electron content in the ionosphere at any given altitude depend on various phenomena such as production and loss rates involving chemical reactions and transport phenomena involving diffusion and drifts.…”
Section: Resultssupporting
confidence: 59%
“…The decrease in the ionization in most ionospheric layers (D, E, F1) is obvious, although each differs in magnitude. The parameter fmin is a measure of the Dregion ionization (Chandra et al, 1997). During the eclipse day fmin values dropped below 1.5 MHz, corresponding to a decrease of about 62% in respect to the normal daytime values.…”
Section: Ionospheric Responsementioning
confidence: 99%